O MUNDO DOS CUSTOS E O MUNDO DOS GANHOS: O ABC E A TOC PODEM COEXISTIR? - Rucinski, Liane; Lima, Paulo Corrêa (Anais do Congresso Brasileiro de Custos - ABC)
The reason of organizations existence is to generate wealth, not to control costs. However, that obvious fact is not reflected in the performance measures adopted by the companies. Indeed, the effect of cost reductions will be realized in the bottom line only if the operacional expenses be reduced as well. Activity Based Costing (ABC) and the Theory of Constraints (TOC) have become two of the hottest trends in manufacturing. The apparent conflict between TOC and ABC stems from the writings of E. M. Goldratt, who portrays cost accounting as the villain preventing companies from obtaining their goal to make more money. TOC´s focus is clear by emphazizing Throughput and Inventory while de-emphasizing Operating Expenses. ABC´s role within the context of a TOC environment is to effectively control operational expenses. Actually, what matters for the companies competitivity and profitabilty is the cost of the whole process, not only the cost of operations. Moreover, production is an integrated process that begins with the supply of materials and components, and continues even after the final product is reached to the end user, then the cost of services is also part of products cost.